Legal Analysis of The Legitimacy of Law Enforcement Intelligence Activities by The Indonesian Prosecution Service Based on The Attorney General’s Instruction No. 7 of 2023 in Handling Corruption Cases in Indonesia - Erwin Efendi Rangkuti; Muhammad Azhali Siregar; Suci Ramadani (Utan Kayu Publishing, 2025)
Corruption constitutes an extraordinary crime due to its pervasive and destructive impact on political stability, economic integrity, and the social order of society. In combating this crime, the Office of the Attorney General of the Republic of Indonesia plays a crucial role not only as a public prosecutor but also as an institution vested with the authority to conduct law enforcement intelligence activities. This authority is generally regulated under Law No. 16 of 2004, as amended by Law No. 11 of 2021 on the Prosecution Service of the Republic of Indonesia. However, such provisions remain too general and fail to provide clear technical guidelines regarding the scope, mechanisms, and oversight of prosecutorial intelligence operations. To optimize this function, the Attorney General issued Instruction No. 7 of 2023, which emphasizes the intelligence function of the Prosecution Service in supporting general criminal law enforcement, special criminal acts, and corruption prevention. Nevertheless, the Instruction remains an internal administrative directive with no binding external legal force. This research adopts a normative juridical method, employing statutory, conceptual, comparative, and case study approaches. The findings reveal that the prosecutorial intelligence function is strategically significant in supporting anti-corruption efforts. However, juridical weaknesses persist, potentially resulting in normative conflicts and risks of human rights violations. Therefore, the study concludes that a statutory-level regulation is necessary to strengthen the legality and accountability of prosecutorial intelligence within Indonesia’s criminal justice system.